ANALISIS KESALAHAN LINGUISTIK DALAM PENERJEMAHAN TEKS BAHASA ARAB PADA GOOGLE TRANSLATE - Marhamah, Aulia; Imas Marliana; Halimah Ibrahim; Sahkholid Nasution (AL-MUADDIB: Jurnal Kajian Ilmu Kependidikan, 2025)
This study aims to analyze linguistic errors in translating Arabic texts. The habit of translating Arabic often uses Google Translate, focusing on morphological, syntactic, and semantic aspects to see the extent of errors in using Google Translate. The research method used is a qualitative method with a content analysis approach to see and explore these problems. Primary data used from testing Arabic texts that have been translated into Indonesian by Google Translate. While secondary data through literature studies. The results of the study show that Google Translate often makes mistakes in understanding the structure and linguistic system of Arabic, which has morphological complexity, flexibility of sentence structure, and semantic nuances that cannot always be translated directly. Morphological errors include misidentification of word forms and vowels, syntactic errors related to structure.